2020
DOI: 10.1038/s41598-020-69104-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an active lifestyle on heart rate variability and oxidative stress markers in offspring of hypertensives

Abstract: Familial history of hypertension is associated with autonomic dysfunction and increase in blood pressure (BP). However, an active lifestyle has been found to improve a number of health outcomes and reduce all-cause mortality. The aim of the present study was to investigate the effects of an active lifestyle on hemodynamics, heart rate variability (HRV) and oxidative stress markers in offspring of hypertensive parents. One hundred twenty-seven subjects were assigned into four groups: sedentary offspring of norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…[ 10 ] People with normal blood pressure who are sedentary and physically inactive have a higher risk of high blood pressure than those who are physically active. [ 11 , 12 ] Psychosocial factors are also associated with hypertension, such as personality, [ 13 ] occupation, [ 14 ] working hours. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] People with normal blood pressure who are sedentary and physically inactive have a higher risk of high blood pressure than those who are physically active. [ 11 , 12 ] Psychosocial factors are also associated with hypertension, such as personality, [ 13 ] occupation, [ 14 ] working hours. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…[81][82][83][84][85][86][87] A reduction in circulating blood levels of catecholamines and angiotensin II has also been observed, 24,25,83,88 in addition to the recovery of endothelial function; increasing bioavailability of nitric oxide (NO); reduction of proinflammatory cytokines, such as TNF-α and IL-6; and low oxidative stress. 79,[89][90][91][92][93][94][95] Another important effect of physical training seems to involve central neural adaptations; autonomic adjustments also derive from effects on central neural nuclei of cardiovascular control, resulting in increased vagal drive and/or a decrease in sympathetic drive and improvement in baroreflex sensitivity. 89,[96][97][98][99][100][101][102] Thus, the sum of local and systemic effects associated with increased cardiovascular fitness results in a more adequate cardiac autonomic modulation, characterized by an increase in HRV.…”
mentioning
confidence: 99%
“…In developed countries, 60% of the population practice sport regularly [ 30 ], in our study only 14% performed physical activity. Recently, Sata Rosa et al showed that an active lifestyle improves heart rate variability, reduces oxidative stress in hypertensive people, and improves BP control [ 31 ]. On the other hand, Beta-blockers should not be dismissed, and patients with high HR definitely need this therapeutic class.…”
Section: Discussionmentioning
confidence: 99%